Unidades didáticas de química e prática docente: quais relações? - Zappe, Janessa Aline (2016)
This thesis describes a research on the educational practice of the author, from the planning, implementation and evaluation of teaching units of Chemistry, considering the conditions of teaching practice. As a basis for the planning of the units, it sought to articles published in national journals of Teaching area on Thermochemistry, Chemical Kinetics and Organic Chemistry, topics studied through the teaching units. In all, fifty articles were analyzed and categorized according to the focus on: conceptual aspects (CA), teaching proposals (TP) and investigations in the classroom (IC), with revisions concepts, experiments and activities involving different themes in room class. From there, the teaching units have been prepared and implemented in a high school class in a school in the central region of Rio Grande do Sul, and educational activities as explanations, exercises, experiments, activities in FISQUIM site, videos and research activities in Internet. After the implementation of the units, the material produced by the students, planning and daily class teacher are used to investigate how can occur articulation of conceptual, procedural and attitudinal content in teaching units. The contents were identified and characterized in the units, and subsequently selected for evaluation. The analysis encompassed conceptual content: endothermic and exothermic phenomena; principle of conservation of energy; reaction rate; factors that affect the rate of reaction; representation of organic compounds; classification of carbon and carbon chains; and hydrocarbon. With respect to the procedural contents, experimental activities on Thermochemistry and Chemical Kinetics and the construction and interpretation of charts and graphs were evaluated. As attitudes were selected responsibility and participate and contribute to the group. As a result of the research, are pointed out: difficulties of concepts implementation related to the endothermic and exothermic phenomena in different contexts, the use of proportional calculation and representation of graphs and charts. Through the evaluation of the contents, is experienced, the process of reflection on reflection-in-action. In adittion, the units can be can replanned. It is proposed to insert the atomic-molecular approach to teaching Thermochemistry and Chemical Kinetics, the use of more experimental activities, working together with teachers of other subjects, the reformulation of questions and the use of problems in the evaluation. In this sense, as consequences of research are mentioned the importance of inserting the process of reflection in initial teacher education and the possibility of integration of the units, working jointly concepts, procedures and attitudes relating to Thermochemistry, Chemical Kinetics and Organic Chemistry .